(untitled) (Research Journal of Padmakanya Multiple Campus, 2024)
Tinospora cordifolia is medicinal plant commonly known as Guduchi or Gurjo with small greenish flowers, having enormous medicinal value in all its parts such as leaves, stem, and also the root. The main objective of this research was designed to assess the antifungal activity of ethanol extraction of T. cordifolia stem of different concentrations by Agar well diffusion method in the microbiology laboratory of Padma Kanya Multiple Campus for the duration of 3 months. In this study, only the stem was selected which was grinded in powder form then extraction was done in ethanol. The extract was diluted in DMSO of different concentration of 2%, 3%, 4%, 5%,6%, 7% and 8%. Preliminary qualitative phytochemical screening was carried out for the presence of tannins, flavonoids and alkaloids. From this study, the extraction of T. cordifolia stem showed the presence of tannins, flavonoids and alkaloids. From various concentrations of 2%, 3%, 4%, 5%, 6%, 7%, and 8% of T. cordifolia , antifungal activity (except for Penicillum spp.) was found to be highly effective in 6%, 7%, and 8% concentrations. This study concluded that the higher concentration of ethanol extraction of T. cordifolia was found to be effective for fungi. Therefore, for further studies, ethanol extraction for T. cordifolia is recommended to be used for antifungal activity.